Pengaruh Nilai Persediaan, Profit Margin, Metode Arus Biaya Persediaan dan Return On Equity Terhadap Market Value - Herpika Oktavia; Andrian Noviardy (Publikasi Indonesia, 2022)
This study aims to provide information about the factors that affect the company's market value. In this research, the writer examines